Multibeam bathymetry from SONNE cruises SO104 and SO244 and Marcus G. Langseth cruise MGL1610 - Geersen, Jacob; Klaucke, Ingo; Behrmann, Jan-Hinrich; Kopp, Heidrun; Tréhu, Anne M; Reichert, Christian (In supplement to: Geersen, Jacob; Ranero, César R; Klaucke, Ingo; Behrmann, Jan-Hinrich; Kopp, Heidrun; Tréhu, Anne M; Contreras-Reyes, Eduardo; Barckhausen, Udo; Reichert, Christian (2018): Active Tectonics of the North Chilean Marine Forearc and Adjacent Oceanic Nazca Plate. Tectonics, 37(11), 4194-4211, https://doi.org/10.1029/2018TC005087, 2018)
Multibeam bathymetric data were acquired during R/V SONNE Cruises SO104, SO244, and R/V Marcus G. Langseth Cruise MGL1610. The datasets were individually processed and gridded with grid cell sizes of 75 m. For the combined grid, depth information from SO244 was used wherever possible. If no SO244 data were available, MGL1610 data were preferred over SO104 data.
Keywords: Bathymetry